A Descriptive Analysis Of The Influence Of Public Sector Corruption On The Privatization Of Nigerian Roads - Yusuff Jelili, Amuda (2016)
The predicament experienced by the majority of commuters as a result of the state of roads across Nigeria is of major concern that must be positively addressed by the authority before it gets out of control. The problem is not limited to a particular geopolitical region, it cuts across the nation. This paper therefore examines the causes and effects of bad roads in Nigeria and considered privatization a key option and the means for provision of good roads. Privatization provides another argument as a solution for reducing public sector corruption and a source of relief on the budget for capital projects. The proffered options are in the interest of the public regardless of the tribe, faith, sect, gender, and status. This discussion is a descriptive approach. The paper concludes by identifiying outstanding problems and offers solutions and suggestions.